Pengenalan Huruf Hijaiyah Melalui Media Flash Card Pada Anak RA Ihyaul Qur’an - Noor, Fu'ad Arif; Istiqomah, Istiqomah (Jurnal Generasi Tarbiyah: Jurnal Pendidikan Islam, 2024)
This study aims to find out and see playing while learning activities through flash card media in improving children's ability to recognize Hijaiyah letters. This study used 17 children aged 4-5 years as participants. The research model used in this study used the Kemmis and M.C Taggart design model using 3 cycles of each cycle using four steps, namely: planning, action, observation and reflection. The results of research using Flash Card media in increasing the ability to recognize children's hijaiyah letters are increasing, namely in the pre-cycle the child's ability is 48.07%, the first cycle the child's ability is 55.76%, the second cycle the child's ability is 80.76%, and the third cycle the child's ability 97.11%. It can be concluded that the use of Flash Card media can improve the ability to recognize children's hijaiyah letters in group A RA Ihyaul Qur'an Krandon Guntur Demak.